A Toolbox for Constructing a Stable Genetic Transformation Platform Allowing Foreign Fragment Integration in the Genome of Neopyropia yezoensis - Cao, Xuexue; Kong, Fanna; Sun, Bin; Yin, Jiqiang; Ren, Hongzhong; Yue, Huijie; Yu, Chenggong; Tang, Xianghai; Du, Guoying; Wang, Dongmei; Mao, Yunxiang (Frontiers in Marine Science, 2022)
Neopyropia yezoensis, previously known as Pyropia yezoensis, is regarded as a model macroalgae because of its economic value and typical intertidal seaweed species. However, the genetic transformation system to introduce foreign genes into its cells is inefficient and not stable. This study developed a more efficient transformation toolbox that allows the stable expression of foreign genes in N. yezoensis cells. We constructed an efficient transformation platform with the parameters of biolistic bombardment of 6 cm target distance, 600 μg gold particles/shot, 10 μg plasmid DNA/shot, 1,350 psi of helium, and 30 mmHg vacuum pressure. Thalli at 35 days of age were the most suitable transformation conditions, in which the highest transformation efficiency was generated. The endogenous promoter pPyACT1 could control gene expression efficiently compared to pPyUBC, pPyDPE2, and pPyEF1-a, especially the exogenous promoter d35S. Finally, the foreign genes PyGUS and PyHygR were stably expressed in different generations of transformants, including monospores, gametophytes, and filamentous sporophytes. Southern blotting analysis confirmed that PyGUS was integrated into the genome of N. yezoensis transformants. Establishing an efficient gene expression toolbox provides a strong foundation for functional genomics research and molecular genetic breeding on N. yezoensis.